Business Cycle and The Macroeconomics Performance: Evidence of Malaysia and Indonesia - Abdul Qoyum; M. Miftahussurur; Al-Amin Matae; Muhammad Yousuf; A. Abdurrahman (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2014)
Stable economic growth is the major macroeconomic goal which is all nations seek. Economist and policy makers have been tried to find the ways to sustain and maintain stable economic growth. This paper examines the macroeconomic fluctuations and economic growth in Malaysia and Indonesia and its determinant by using multiple regression models. Five variables were chosen for the model namely variables are Money supply (MS), Industrial production (IP), Interest rate (IR), exchange rate (ER), Consumer price Index (CPI) and stock prices. The study shows that Money supply (MS), Interest rate (IR), exchange rate (ER), and stock prices are among others, the determinant factors of macroeconomic fluctuations in both countries. Specifically, the empirical results reveal that Interest rate (IR), exchange rate (ER), and stock prices has significant contribution to the performance of real GDP in Malaysia while Money supply (MS) and exchange rate (ER) are the main cause of macroeconomic fluctuations in Indonesia. This may be due to the different monetary policies pursued by the two countries. The two countries might have different monetary policy strategies; Malaysia pursues interest rate targeting policy, whereas Indonesia applies inflation rate targeting policy.The study recommends for both countries government policies play an important role in economic performance. Therefore, a careful policy should be the foremost important factor for economic in these nations and the every country in general.